rickyjohny
rickyjohny
02-10-2016
Mathematics
contestada
solve -4(6x+3)=-12(x+10)
Respuesta :
gavee
gavee
02-10-2016
-24x-12 = 12x+120. -36x= 132. x= 132/-36 = -3.6
Answer Link
PrinceBrainly
PrinceBrainly
02-10-2016
Hello there.
Solve -4(6x+3)=-12(x+10)
x=
9
Answer Link
VER TODAS LAS RESPUESTAS ( 95+ )
Otras preguntas
For a population with µ = 80 and σ = 20, the distribution of sample means based on n = 16 will have an expected value of __________
What is the ongoing set of competitive actions and competitive responses that occur among firms as they maneuver for an advantageous market position?
Fire __________ systems are devices installed and maintained to detect and respond to a fire, potential fire, or combustion danger situation.
If all the assumptions underpinning the policy irrelevance proposition are in place, fully anticipated monetary policy will:____.
Find the extremum of f(x,y) subject to the given constraint, and state whether it is a maximum or a minimum. f(x,y)=3y2−3x2; 2x y=9
If your risk aversion index a = 4, what is your optimal allocation between risky asset p ( ) and risk-free asset (1- )?
Identify ER rounded to the nearest tenth. The Figure shows right triangle M E R with right angle E. The length of hypotenuse M R is equal to 37 units. Angle R m
Each of the gears a and b has a mass of 675 g and has a radius of gyration of 40 mm, while gear c has a mass of 3. 6 kg and a radius of gyration of 100 mm. Assu
Jon's health plan pays benefits of 90or in-network providers and 70or out-of-network providers. what kind of plan is this?
Sperm release ________ to break down the bonds between adjacent follicle cells surrounding the oocyte